(untitled) (Medico Legal Update, 2020)
Assessment of presence of the phenotypic characteristic of Polycystic Ovarian Syndrome among young adult girls in a selected college in Kanchipuram District, Tamil Nadu. The Objectives are to assess the phenotypic characteristics of polycystic ovarian syndrome among young adult girls. To determine the association between phenotypic characteristics with selected demographic variables. The convenience sampling technique was used to select 295 sampling. Validity and Reliability data collection tools were established. The data were collected by self-structured questionnaires. The collected data were tabulated and analyzed. The findings of the present study Shows that the presence of phenotypic characteristics of PCOS based on score of hirsutism was estimated to be (39.7%) and based on grading of acne was estimated to be (66.8%) of young adult girls have mild acne characteristics of PCOS, (13.5%) of young adult girls have moderate acne characteristics of PCOS.(11.9%) have severe acne characteristics of PCOS and (7.8%) have very severe acne characteristics of PCOS. There is significant association between the demographic variables and the scoring of hirsutism of young adult girls in their age, residence, age of menarche, regulation of menstrual cycle, length of menstrual cycle, BMI at p value= <0.05 level of significant. And there is significant association between demographic variables and the grading of acne among young adult girls in their residence, menstrual cycle, length of menstrual cycle, family history of PCOS, co-morbidities, BMI at p value= <0.05% level of significant.